2011
DOI: 10.4137/bic.s7151
|View full text |Cite
|
Sign up to set email alerts
|

Organic Anion Transporting Polypeptide 5A1 (OATP5A1) in Small Cell Lung Cancer (SCLC) Cells: Possible Involvement in Chemoresistance to Satraplatin

Abstract: BackgroundThe role of organic anion transporting polypeptide 5A1 (OATP5A1) a member of a family of drug transporters that mediate cellular uptake of drugs has not been characterized so far.MethodsGene expression levels of OATP5A1 in small cell lung cancer (SCLC) cell lines were determined by real-time qPCR and chemosensitivity of HEK-293-SLCO5A1-transfected cells to satraplatin in MTT assays.ResultsSignificant expression of this transporter was found at the mRNA level, primarily in drug-resistant SCLC cells, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 30 publications
(59 reference statements)
1
13
0
Order By: Relevance
“…Immunohistochemical analyses confirmed that OATP5A1 is expressed on the membrane and in the cytoplasm of breast cancer cells (89). OATP5A1 at both the mRNA and protein levels was found to be upregulated in liver cancer (80) and small cell lung cancer (SCLC) (5). As a potential marker of chemotherapy resistance, HEK-293 cells transfected with OATP5A1 showed resistance to satraplatin treatment (5).…”
Section: Oatp5a1 (Gene Symbol Slco5a1)mentioning
confidence: 83%
See 2 more Smart Citations
“…Immunohistochemical analyses confirmed that OATP5A1 is expressed on the membrane and in the cytoplasm of breast cancer cells (89). OATP5A1 at both the mRNA and protein levels was found to be upregulated in liver cancer (80) and small cell lung cancer (SCLC) (5). As a potential marker of chemotherapy resistance, HEK-293 cells transfected with OATP5A1 showed resistance to satraplatin treatment (5).…”
Section: Oatp5a1 (Gene Symbol Slco5a1)mentioning
confidence: 83%
“…OATP5A1 at both the mRNA and protein levels was found to be upregulated in liver cancer (80) and small cell lung cancer (SCLC) (5). As a potential marker of chemotherapy resistance, HEK-293 cells transfected with OATP5A1 showed resistance to satraplatin treatment (5). Further studies may be warranted to elucidate the impact of OATP5A1 on tumor resistance and better understand the role OATP5A1 in cancer.…”
Section: Oatp5a1 (Gene Symbol Slco5a1)mentioning
confidence: 99%
See 1 more Smart Citation
“…There is some evidence that OATP5A1 is involved in the chemoresistance to the oral anticancer drug satraplatin [15]. …”
Section: The Oatp Family Of Transportersmentioning
confidence: 99%
“…OATP1A2, 1B1, 1B3 and 2B1 transport a wide range of compounds, from bile acids and hormones, to various therapeutics including statins, antiviral agents and antibiotics. Conversely, OATP3A1, 1C1, 2A1, 4A1, 4C1 and 5A1 have been documented to transport only a few compounds [4, 6, 7]. Currently, there is no published information on the function or substrate specificity of OATP6A1, primarily due to the lack of convenient expression systems and functional assays.…”
Section: Introductionmentioning
confidence: 99%